Hiding in plain sight: the 'relationship' in peer assisted learning in higher education - Ana Garcia-Melgar (Association for Learning Development in Higher Education (ALDinHE), 2015)
Relationships underpin peer learning; however, they remain under-researched and under -theorised. We propose a model to identify factors that contribute to relationships in Peer Assisted Learning (PAL). Our model integrates three discrete bodies of knowledge: previous studies of PAL affordances, a synthesis of understandings drawn from learning theories, and studies of peer relationships in business and education. Our model features two components: social and cognitive congruence that deliver sustained PAL improvements. To evaluate the contributions of social and cognitive congruence to successful PAL outcomes, we evaluated four theoretical scenarios based on presence and/or absence of these factors. In each case, variations in social and cognitive congruence and mediating factors can potentially vary the quality of learning outcomes, student interactions, and engagement in PAL. Our scenarios can be employed to evaluate areas of targeted improvement in PAL. We discuss the implications of our model for PAL research and practice.